Questioning ethnic fragmentation's exogeneity: Drivers of changing ethnic boundaries - Philipp Kolo (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2011)
Ethnic fragmentation is a variable increasingly used in the economic literature to explain differences in economic development level, growth or the incidence of conflicts. Nearly all articles have in common that they treat ethnic fragmentation as a static, exogenous fact. Only recently some contributions outlined first ideas, why different levels of ethnic fragmentation evolved based on biodiversity and evolutionary theories. This article has two main goals. In connecting with these recent findings, the article boldly confirms their results that a 'base-level' of fragmentation evolved due to geographical and evolutionary factors. Additionally, it draws the attention to the impact of colonization on fragmentation, especially on how a country was colonized. The main goal, however, is to show that ethnic fragmentation is not only evolving over centuries, but changes over a short period of time. As static factors, e.g. geographical ones, can't be responsible for changes in the short run, the article offers a structured assessment of factors that may influence diversity levels in the short term. Although migration is the most obvious factor, urbanization and especially education play an even more important role in influencing a country's ethnic boundaries.
Keywords: C23; F54; I29; O10; Z10; 330; Colonization; Endogeneity; Ethnic fractionalization (ELF); Heterogeneity; Ethnische Beziehungen; Evolutionsökonomik; Kolonialismus; Schätzung; Welt